Antidiabetic Activity of Diospyros mespiliformis on Alloxan-Induced Diabetic Rats - Dahiru, Mubarak Muhammad; Musa, Neksumi (Universitas Muhammadiyah Yogyakarta, 2024)
The rate of morbidity and mortality attributed to diabetes has become a concern and challenge for individuals and governments. The availability, affordability, and efficacy of plant-based drugs make them an attractive choice for diabetic management in low-income countries and rural communities. Thus, their application in folkloric medicine for diabetic management. This study investigated the antidiabetic activity of the crude ethanol extract (CRE), ethyl acetate (EAF), and aqueous (AQF) fractions Diospyros mespiliformis (DM) in alloxan-induced diabetic rats to justify its acclaimed applications in folkloric medicine. The effect of the plant extract and its fractions on the aspartate aminotransferase, glutamyl aminotransferase, albumin, urea, creatinine, electrolytes, and lipid profile was determined by biochemical assay methods. The result showed a significant (p 0.05) decrease in fasting blood glucose for all the extracts, while the aspartate aminotransferase, gamma-glutamyl transferase, and albumin were significantly (p 0.05) decreased in the EAF only. The urea and creatinine levels of the CRE and AQF were decreased significantly (p 0.05), while K+, Cl-, and HCO3- levels decreased significantly (p 0.05) for the treatment groups. Furthermore, a significant (p 0.05) decrease in total cholesterol and triglyceride was observed for the EAF. Conclusively, DM exhibited significant hypoglycemic and hypolipidemic potential with improved lipid profile and hepato-renal function. Thus, the observed antidiabetic activity of the plant might justify its acclaimed utilization in the treatment/management of diabetes and its related ailment.